Saline–alkaline resistance analysis of rice overexpressing the CsCYP1A gene of alkaline Chlorella. (27th March 2020) - Liu, Jiali; He, Mingliang; Liu, Chenxi; Liao, Xu; Li, Xiufeng; Wang, Ling; Guan, Qingjie
Abstract: Plant cyclophilin (CYP) is related to chloroplast photoprotection, redox and other growth and developmental regulatory processes and responds to stress and improves tolerance to saline–alkali stress. Besides, it exerts peptidyl-prolyl cis / trans isomerase activity to participate in protein synthesis and folding. In this study, Northern blot was used to analyse the CsCYP1A gene (a CYP gene isolated from a Chlorella species) (accession number: KY207381) of tolerant Chlorella vulgaris in soda saline–alkali soil. The result showed that the expression of the CsCYP1A gene was induced by NaHCO3, NaCl and sorbitol. Additionally, Agrobacterium tumefaciens was used to infect the callus of rice ( Oryza sativa var. Longjing11) for genetic transformation. Molecular detection confirmed that transgenic seedlings overexpressing CsCYP1A were obtained by hygromycin selection. Treatment with NaCl and NaHCO3 at the five-leaf stage was performed in the seedlings, and the results showed that there were significant differences between the CsCYP1A overexpressed rice lines and non-transgenic (NT) Longjing11 in terms of plant height, fresh weight, chlorophyll content, malondialdehyde content and ascorbate peroxidase activity. The CsCYP1A overexpression rice lines had higher tolerance to NaCl and NaHCO3 than NT. The current findings indicate that CsCYP1A can enhance the tolerance of rice to saline–alkali stress possibly through its involvement in reactive oxygen scavenging pathways.